قاعدة الحكم الشرعي يدور مع علته وجودا وعدما دراسة تأصيلية تطبيقية )باب الطهارة أنموذجا - بن سالم, عبد الرزاق (جامعة الوادي university of eloued, 2017)
الحمد لله رب العالمين، والصلاة والسلام على رسول الله نبينا محمد وآله وصحبه أجمعين. أما بعد: فهذه الرسالة تناولت بالدراسة قاعدة: الحكم يدور مع علّته وجودا وعدما بالتأصيل والتطبيق. فقد وضحت الدراسة في جانبها التأسيسي مفهوم القواعد الفقهية من خلال التعريف اللّغوي والاصطلاحي، كما بينت أهمّية القواعد الفقهية، وكذلك تعرضت الدراسة إلى القاعدة محلّ الدراسة وبينت أهميتها والأدلّة الشرعية التي تشهد لها، ثم تعرضت إلى التغير في الأحكام الشرعية وهو حاصل العمل بالقاعدة الفقهية وعرفته وبينت أنواعه وضوابطه . ثم تعرضت الدراسة للقاعدة من أهم زواياها وهو الحكم وبينت تعريفه وأقسامه، ثم العلّة، التي تناولتها الدراسة من خلال التعريف بالعلّة، ثم طرق معرفتها (مسالك العلّة) وتخلّل ذلك تحقيقات علمية لكثير من المسائل الأصولية ذات الصلة بالعلّة وشروطها وضوابطها، وبمسالكها والانتقادات التي توجه إليها، ثم أساس العمل بالقاعدة وهو الدوران، فعرفته وبينت أقوال العلماء في حجيته. ثم تعرضت الدراسة للقاعدة من الناحية التطبيقية العملية، فأدرجت بعض المسائل وحرصت أن تكون متنوعة بين المسائل التقليدية ومسائل النوازل المعاصرة، وذلك إعمالا لهذه القاعدة بغية إظهار أهميتها عمليا بعد إظهار أهميتها من الناحية النظرية. وانتهت الدراسة بخاتمة لخّصت أهم المحطات التي مرت ا الدراسة، وزينت الدراسة بفهرس للآيات، وفهرس للأحاديث والآثار، وفهرس للأعلام المترجم لهم، ثم فهرس المصادر والمراجع.Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the Messenger .of Allah, our Prophet Muhammad and his family and companions After that: This thesis dealt with the study rule: the rule revolves with the burden of .existence and infallibility, rooting and application The study clarified in its founding part the concept of jurisprudential rules through the linguistic and theological definition, as well as the importance of jurisprudential rules, and the study was subjected to the rule under study and showed its importance .and the legal evidence that it attests to. Types and controls Then the study of the rule of the most important angles, which is the rule and defined the definition and sections, and then the bug, which dealt with the study through the definition of the bug, and then methods of knowledge (pathways), and permeated the scientific investigations of many of the fundamental issues related to the disease and conditions and controls, and conduct and criticisms that guide And then the basis of .the rule, which is rotation, and knew him and showed the scientists in his argument The study was then applied to al-Qa'ida in practical terms. It included a number of issues and varied antagonisms between the traditional issues and contemporary issues of inferiority, in pursuance of this rule in order to show its practical significance after .demonstrating its importance in theory The study ended with a summary of the most important stations passed through the study. The study included a catalog of the verses, a catalog of the hadiths and .anecdotes, a catalog of the translated media, and a catalog of references and sources
مذكرة
Keywords: قاعدة الحكم-)باب الطهارة-علته وجودا; The Rule of Judgment-) The Chapter on Purity - Its Cause and Existence